2018
DOI: 10.3389/fnhum.2018.00425
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Neurocognitive Mechanisms Underlying the Processing of Center-Embedded and Non–embedded Musical Structures

Abstract: In music, chords are organized into hierarchical structures based on recursive or embedded syntax. How the brain extracts recursive grammar is a central question in musical cognition and other cognitive neuroscience, but the precise mechanism remains unclear. By analyzing event related potentials (ERPs) and neural oscillatory activity, the present study investigated neurocognitive mechanisms underlying the processing of center-embedded structure in music by examining the differences in center-embedded and non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 85 publications
1
7
0
Order By: Relevance
“…LPC is an ERP correlate of syntactic processing in language (Friederici et al, 1993 ; Kaan et al, 2000 ; Hahne, 2001 ; Mueller et al, 2005 ; Phillips et al, 2005 ) and music (Patel, 1998 ; Neuhaus, 2013 ; Sun et al, 2018 ), reflecting the integrative process and the cognitive resources allocation. Evidence of LPCs for the processing of non-adjacent tonal integration is also given by previous research on musical syntax violation (Koelsch et al, 2013 ; Ma et al, 2018a , b ; Zhou et al, 2019 ). The LPC effect observed in our study may be ascribed to the more cognitive resources required by combining local information into higher global hierarchical units for the nested structure than the non-nested structure.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…LPC is an ERP correlate of syntactic processing in language (Friederici et al, 1993 ; Kaan et al, 2000 ; Hahne, 2001 ; Mueller et al, 2005 ; Phillips et al, 2005 ) and music (Patel, 1998 ; Neuhaus, 2013 ; Sun et al, 2018 ), reflecting the integrative process and the cognitive resources allocation. Evidence of LPCs for the processing of non-adjacent tonal integration is also given by previous research on musical syntax violation (Koelsch et al, 2013 ; Ma et al, 2018a , b ; Zhou et al, 2019 ). The LPC effect observed in our study may be ascribed to the more cognitive resources required by combining local information into higher global hierarchical units for the nested structure than the non-nested structure.…”
Section: Discussionsupporting
confidence: 60%
“…Until recently, Koelsch et al ( 2013 ) first explored the neural responses to the processing of nested structure and found that structurally irregular endings elicited larger early right anterior negativity (ERAN) and N5 components than structurally regular endings, reflecting the structural integration for long-distance dependence. Similar components, such as N5 and late positive component (LPC), were also observed in music nested structure processing by Chinese listeners (Ma et al, 2018a , b ; Zhou et al, 2019 ). These results demonstrated the integration of harmonic cadence into the originally tonal context and the cognitive processing of nested structure.…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations